Advanced optimization load frequency control for multi - islanded micro grid system with tie-line loading by using PSO - Pavan, Gollapudi; Babu, A. Ramesh; Prabhakar, Bollu; Venkata Sai, T. Datta; Rajeshwari, M.; Reddy, N. Raj; Kishore, P. Venkata (Institute of Advanced Engineering and Science, 2025)
This manuscript presents the design of a microgrid featuring solar and wind as uncontrollable energy sources, alongside controllable sources like batteries and a diesel generator, aiming to address power supply variations resulting from load fluctuations. Controllers are imperative to mitigate these challenges, and the manuscript emphasizes the need for precise tuning of gain values for optimal electrical energy utilization. In lieu of the trial-and-error approach, particle swarm optimization (PSO) is employed for enhanced steady-state response in the Microgrid. The study also introduces the application of proportional-integral (PI), proportional-integral-derivative (PID), and PID with feed forward (PIDF) controllers to effectively address and resolve identified issues ensuring improved system performance and consistent power supply stability in the microgrid system.